Decreased lactate and potassium levels in natural moisturizing factor from the stratum corneum of mild atopic dermatitis patients are involved with the reduced hydration state - Sugawara, Tomoko; Kikuchi, Katsuko; Tagami, Hachiro; Aiba, Sestuya; Sakai, Shingo (Journal of dermatological science, 2012)
Atopic dermatitis (AD) shows dry skin. Water-soluble, low molecular weight components, collectively known as natural moisturizing factor (NMF), play an important role in maintaining the stratum corneum (SC) hydration. Previous studies focused on reduced levels of free amino acids (FAAs) in NMF from AD skin. It remains unknown, however, whether other NMF components are also altered in AD. To characterize the levels of various NMF components in the SC of healthy subjects and in mild AD adult patients. NMF components were extracted from three sequential tape-stripped SC samples obtained from the volar forearm. NMF components which were decreased in AD skin were topically applied to examine their contribution to SC moisturization in AD skin. We found that although FAAs levels were not remarkably reduced, levels of pyrrolidone carboxylic acid (PCA), lactate, urea, sodium and potassium were significantly decreased in NMF from mild AD skin. Among those components, only the topical application of potassium lactate effectively increased skin surface hydration indicating that reductions of lactate and potassium influence dry skin in mild AD patients. Unlike the distribution of filaggrin-derived FAAs and PCA, lactate, urea, potassium and sodium were abundant in the surface layer of the SC compared with the inner layer of the SC. Such findings strongly suggest that those components are supplied from outside the SC, i.e. they originate from sweat. The reduced levels of sweat-derived NMF components in mild AD patients suggests that impaired sweat function might in part result in the SC dryness.